Increasing Full Child Immunization Rates by Government Using an Innovative Computerized Immunization Due List in Rural India - Enakshi Ganguly MD; Rahul Gupta MStat; Alik Widge MD, PhD; R. Purushotham Reddy MBA; K. Balasubramanian PhD; P. S. Reddy MD (SAGE Publishing, 2018)
Increasing child vaccination coverage to 85% or more in rural India from the current level of 50% holds great promise for reducing infant and child mortality and improving health of children. We have tested a novel strategy called Rural Effective Affordable Comprehensive Health Care (REACH) in a rural population of more than 300 000 in Rajasthan and succeeded in achieving full immunization coverage of 88.7% among children aged 12 to 23 months in a short span of less than 2 years. The REACH strategy was first developed and successfully implemented in a demonstration project by SHARE INDIA in Medchal region of Andhra Pradesh, and was then replicated in Rajgarh block of Rajasthan in cooperation with Bhoruka Charitable Trust (private partners of Integrated Child Development Services and National Rural Health Mission health workers in Rajgarh). The success of the REACH strategy in both Andhra Pradesh and Rajasthan suggests that it could be successfully adopted as a model to enhance vaccination coverage dramatically in other areas of rural India.